DIVERSITY OF THE EXECUTIVE BOARD, INVESTMENT DECISIONS, AND FIRM VALUE: IS GENDER IMPORTANT IN INDONESIA? - Yuliana, Indah; Kholilah, Kholilah (Jurnal Reviu Akuntansi dan Keuangan)
The purposes of this research are to determine the effect of executive board gender diversity on firm value. Gender diversity shows that companies do not discriminate while evaluating employee performance. This diversity affects the fair competition conducted by employees to show the best performance so they can occupy the highest positions in the company. Gender diversity has the impact of a difference in the level of optimism, confidence, and risk preferences. The feminine nature of women influences the quality of investment decision making, which has an impact on increasing company value. The signalling theory is used to describe the stakeholders perceived on investment decision making by female CEOs. Research using PLS in LQ45 registered companies in Indonesian Stock Exchange for the years 2014-2017. The results showed that investment decisions affect the value of the firm. Besides, the composition of the female CEO can moderate the relationship between investment decisions and firm value. The results of the research have implications for the support of increasing gender diversity in companies because the patriarchal culture adopted in Indonesia causes male domination in decision making both in the family, community or the working environment.